Production and characterization of copper periodic open cellular structures made by 3D printing‐replica technique. Issue 4 (14th September 2020) - Balzarotti, Riccardo; Bisaccia, Alessandra; Tripi, Maria Celeste; Ambrosetti, Matteo; Groppi, Gianpiero; Tronconi, Enrico
Abstract: Additive manufacturing by 3D printing comprises a set of methods for production of 3D objects starting from a CAD file. Advantages of additive manufacturing combine high manufacturing resolution, a reduction of waste material, and the possibility of computer‐aided design (CAD). When applied to the manufacturing of structured catalyst substrates, the latter enables the optimization of transport properties of the catalyst support. Despite several methods have been introduced for a variety of materials, copper, well known for its high thermal conductivity, is still difficult to be handled. In this work, a novel approach for the additive manufacturing of copper periodic open cellular structures (POCS) is proposed and investigated. It consists in the use of the replica manufacturing procedure starting from resin supports produced by 3D printing stereolithography. Micrometric high purity copper powder was effectively dispersed using a liquid medium based on organic components; the resulting slurry was used for the washcoat deposition on the resin supports. Structures with diamond unit cell shape (cell size of 2.5 mm and void fractions in the 0.8‐0.9 range) were washcoated by dip‐spin coating. Homogeneous washcoat layers were obtained without occurrence of cell clogging phenomena. Optimized thermal treatment procedure was assessed for sintering the copper POCS. The resulting matrices preserved the morphology of the original structure, reaching a resolution in the range of 70 to 120 μm. These materials can eventually be used as catalyst supports for heat‐transfer limited applications (eg, steam reforming of methane), where copper‐based substrates were demonstrated to be an effective solution for process intensification. Abstract : Periodic open cellular structures (POCS) are promising supports for intensification of nonadiabatic processes. A novel approach for the production of highly conductive copper‐based POCS is proposed, based on the 3D printing‐replica technique. A suitable slurry formulation is proposed to disperse copper powder and to washcoat POCS produced by 3D stereolithography. A dedicated thermal treatment process is assessed: samples of different cell size are effectively produced, reaching a strut thickness in the 70 to 120 μm range.